Monocytopenia; Induction by Vinorelbine, Cisplatin and Doxorubicin in Breast, Non-Small Cell Lung and Cervix Cancer Patients - Nazir, Taha (Int J Health Sci (Qassim), 2016)
BACKGROUND: The neoplasm is still a potential threat for breast, Non-Small Cell Lung (NSCL) and cervix cancer patients. Those gradually invade into other body organs, inducing complex pathological complications. Whereas, the anticancer drugs suppress the bone marrow, resulting serious hematological toxicities. Thus, the monocytic toxicity may the chance of infections, particularly in AID’s patients. OBJECTIVE: We aimed this retrospective study to investigate the monocytopenia induced by vinorelbine following chemotherapy in cancer patients. PATIENTS AND METHOD: A total 60 adult cancer patients were divided into two groups; Group-1 patients received the treatment of Vinorelbine alone while group 2 patients received Vinorelbine based combination chemotherapy. RESULT: The overall comparison of mean monocyte count (×10(3) per μl) with time showed a significant statistical difference (p value <0.001) for G-I and no significant difference for G-II (p value <0.08). The independent comparison of mean values for two groups at every week confirms the non-significant statistical difference during all of the five weeks (p values 0.551, 0.112, 0.559, 0.372, 0.468 respectively). In addition of that, the comparison of mean values observed before therapy with that of week 4 (after therapy) showed significant difference in G-I (p value <0.001) and non-significant in G-II (p value 0.053). CONCLUSION: Monocytopenia is induced in both of the chemotherapy protocols allows the clinical oncologists and consultant physicians to select either of the chemotherapy protocol. The therapeutic efficacy should constitute the intervening consideration to treat the breast, cervix and NSCL (Non-Small Cell Lung’s) cancers.